Sofrimento psíquico em estudantes de medicina : uma leitura psicanalítica para uma educação humanizadora - Funghetti, Ana Luíza (2025)
The objective of this dissertation is to study the psychological suffering of medical students during their training and to explore perspectives for a humanizing medical education. The guiding question is formulated as follows: how does psychological suffering manifest during medical training, and what perspectives can be considered towards a humanizing education that acknowledges and alleviates such suffering? Methodologically, the research is a descriptive case study based on the evidence from multiple studies addressing this phenomenon. As a strategy: (a) we conducted an exploratory bibliographic research, which grounds the issue under study through existing publications; (b) we carried out a survey of the socio-identity profile of students through information gathered via an electronic Google form and a printed version; and (c) we collected qualitative data using focus group methodology, through which students expressed their experiences during training and had the opportunity to discuss what causes suffering. In the first step, the study describes significant experiences in the history of medicine, shows the current profile of medical students, and details the construction of the methodological approach in the three planned stages. In the second step, it explores the relationship between medical students’ education, mental health, and psychological suffering, considering some challenges arising from the traditional model of education. In this step, the study also delves into aspects of students' mental health and possibilities for humanizing education, along with a detailed presentation of the results from the three focus groups conducted, analyzing their connection to the learning environment, pedagogical and human relationships, and mental health. a) Suffering is not associated with a specific practice location, nor with the complexity of tasks to be learned, but its triggering factor is primarily the quality of the relationship with the professor; b) The existence of hostile and abusive behavior in the pedagogical relationship hinders the student’s connection with the professor, leading to the erasure of the individual; c) In contexts of psychological suffering, students feel invisible and excluded, perceiving themselves in an objectified relationship; d) The lack of pedagogical training among some faculty members, combined with the discourse of power, distances students from the professor; e) When professors have pedagogical training, they are perceived as the primary agents in building a humanizing education, performing their role through dialogue, listening, and understanding, recognizing the student’s individuality and subjectivity.